2006
DOI: 10.3168/jds.s0022-0302(06)72258-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Casein Micelles Cross-Linked by Transglutaminase

Abstract: In this study, caseins micelles were internally cross-linked using the enzyme transglutaminase (TGase). The integrity of the micelles was examined on solubilization of micellar calcium phosphate (MCP) or on disruption of hydrophobic interactions and breakage of hydrogen bonds. The level of monomeric caseins, determined electrophoretically, decreased with increasing time of incubation with TGase at 30 degrees C; after incubation for 24 h, no monomeric beta- or kappa-caseins were detected, whereas only a small l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 39 publications
(47 reference statements)
6
70
0
Order By: Relevance
“…In spite of studies that have shown an order of β-casein > α S -casein > κ-casein, e.g., [77,78,80], this information is still cited in the literature, e.g., [27,102]. On the other hand, it is generally acknowledged that κ-casein is most susceptible to TGase in case of micellar casein because of high accessibility on the micelle surface, e.g., [78,92,[103][104][105][106][107][108]. This was also shown for cross-linking with laccase [35,98,99].…”
Section: Literature Review Of Studies On Cross-linked Caseinmentioning
confidence: 85%
See 1 more Smart Citation
“…In spite of studies that have shown an order of β-casein > α S -casein > κ-casein, e.g., [77,78,80], this information is still cited in the literature, e.g., [27,102]. On the other hand, it is generally acknowledged that κ-casein is most susceptible to TGase in case of micellar casein because of high accessibility on the micelle surface, e.g., [78,92,[103][104][105][106][107][108]. This was also shown for cross-linking with laccase [35,98,99].…”
Section: Literature Review Of Studies On Cross-linked Caseinmentioning
confidence: 85%
“…Corresponding bands may also be identified in mixed system, but overall resolution is rather poor because the variety of heteropolymers causes a pronounced smear. Furthermore, very large polymers cannot penetrate the separating or stacking gel and remain as condensed stains at the top (Figure 7a,b; see also [89][90][91], which may even result in a loss of sample material [92,93]. The separation limit can be slightly expanded by decreasing the pore size of the gel matrix (reduction of acrylamide concentration) or by using a gradient gel (compare Figure 7a,b), but a thorough analysis of high molar mass casein polymers by SDS-PAGE is not possible since even low acrylamide concentrations of typical stacking gels (40 mg/mL) can hardly be reduced without limiting practicability.…”
Section: Advantages and Limitations In The Context Of Casein Investigmentioning
confidence: 99%
“…For micellar casein, the order of susceptibility to TGase-induced cross-linking is κ-CN > β-CN > α s -CN, which is predominantly related to the easy of accessibility of the caseins for the enzyme [131]. Lightscattering measurements have shown that, in unconcentrated milk, cross-linking of micellar caseins is exclusively intramicellar and not inter-micellar [64].…”
Section: Applications Of Transglutaminase In Cheese-makingmentioning
confidence: 99%
“…Lightscattering measurements have shown that, in unconcentrated milk, cross-linking of micellar caseins is exclusively intramicellar and not inter-micellar [64]. This intra-micellar cross-linking stabilizes the micelle against disintegration under unfavourable conditions [64,131] and also has major implications for the hairy brush, consisting predominantly of κ-CN, which provides colloidal stability to the micelle [64].…”
Section: Applications Of Transglutaminase In Cheese-makingmentioning
confidence: 99%
“…insoluble phosphoproteins organized in complex multi-molecular aggregates, named micelles, that at certain conditions of temperature and acidity (T ~ 20 ºC, pH = 4.6), precipitate from skim milk (Thompson et al 1965). Besides caseins, micelles contain inorganic materials such as calcium phosphate and calcium citrate (Smiddy et al 2006). In ruminants, four casein types have been distinguished so far : S1-casein (CSN1S1), S2-casein (CSN1S2), -casein (CSN2) and κ-casein (CSN3).…”
Section: Introductionmentioning
confidence: 99%